2001
DOI: 10.1080/00034980120103414
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers for chloroquine-resistant Plasmodium falciparum malaria in Thailand and Laos

Abstract: Chloroquine-resistant Plasmodium falciparum is well documented in Thailand. Laos, however, continues to use chloroquine (CQ) as the first-line therapy for the treatment of P. falciparum malaria. The objective of the present study was to determine the prevalence, in these two areas, of the cg2, pfmdr1 and pfcrt allelic types that have previously been associated with CQ resistance. Isolates of P. falciparum were collected from participants in ongoing treatment studies conducted in Thailand (near the Thai-Cambodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
3
12
1
Order By: Relevance
“…This observation supports the view that the pfcrt polymorphism at position 76 is in fact a significant factor of CQ resistance, as shown in previous studies from Cameroon, 13 Mali, 8 Mozambique, 10 Nigeria, 20 Sudan, 12 Uganda, 9,21 Madagascar, 22 Laos, 11,23 Papua New Guinea, 14,24 and Thailand. 14,23 The proportion of children infected with parasite clones carrying the pfcrt T76 variant decreased significantly with age and correlated with the age-associated decrease in CQ levels. The higher levels of CQ in younger children might result from the fact that these children are more frequently given CQ when they are febrile during an assumed malaria attack.…”
Section: Discussionsupporting
confidence: 77%
“…This observation supports the view that the pfcrt polymorphism at position 76 is in fact a significant factor of CQ resistance, as shown in previous studies from Cameroon, 13 Mali, 8 Mozambique, 10 Nigeria, 20 Sudan, 12 Uganda, 9,21 Madagascar, 22 Laos, 11,23 Papua New Guinea, 14,24 and Thailand. 14,23 The proportion of children infected with parasite clones carrying the pfcrt T76 variant decreased significantly with age and correlated with the age-associated decrease in CQ levels. The higher levels of CQ in younger children might result from the fact that these children are more frequently given CQ when they are febrile during an assumed malaria attack.…”
Section: Discussionsupporting
confidence: 77%
“…Our in vitro observations show a near total prevalence of CQR (96%) in the present study area, confirming what has been widely reported [1]. Among all CQR isolates tested in our study, the presence of pfcrt 76T was universal ( P = 0.001), indicating complete selection of this polymorphism by the drug, a result that is in agreement with recently published work not only from Thai-originated parasites [22], but also from parasites of different areas of the globe [32]. …”
Section: Discussionsupporting
confidence: 93%
“…Several studies have shown that more than 50% of Thai isolates are resistant to MQ in vitro, and that the prevalence of the D10-like N1042 and D1246 pfmdr1 polymorphisms is greater than 90% (Price et al, 1999;Lopes et al, 2002;Price et al, 2004), consistent with both a fitness advantage in the absence of CQ and previous observations associating MQ resistance with these polymorphisms (Duraisingh et al, 2000b;Reed et al, 2000). Despite the prevalence of the wild-type (CQS) pfmdr1 allele, in vivo CQ resistance in Thailand remains high, probably as a consequence of the CQR-conferring K76T mutation in PfCRT having reached near-fixation throughout the country (Price et al, 1999;Labbe et al, 2001;Lopes et al, 2002).…”
Section: Discussionmentioning
confidence: 48%
“…Therefore in areas where the treatment for malaria includes MQ but not CQ, parasites with mutations at pfmdr1 codons 1034, 1042 and 1246 would be doubly disadvantaged with respect to parasites with the wild-type pfmdr1 allele, in terms of both decreased fitness and heightened drug sensitivity. This is borne out by recent findings in Thailand, where use of CQ as the first-line treatment for falciparum malaria was discontinued in 1972 in favour of Fansidar (a combination of the antifolate drugs sulfadoxine and pyrimethamine), which in turn was replaced by Fansimef (MQ with sulfadoxine/pyrimethamine) in 1985 (Thaithong et al, 1988;Labbe et al, 2001). Several studies have shown that more than 50% of Thai isolates are resistant to MQ in vitro, and that the prevalence of the D10-like N1042 and D1246 pfmdr1 polymorphisms is greater than 90% (Price et al, 1999;Lopes et al, 2002;Price et al, 2004), consistent with both a fitness advantage in the absence of CQ and previous observations associating MQ resistance with these polymorphisms (Duraisingh et al, 2000b;Reed et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation